(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the results of some maternal and child health care activities, and family planning at the My Loc commune health station, Hau Loc district, Thanh Hoa province from 2015 to 2023. Methods: Analyze secondary data. Results: The female ratio during the period (2015 - 2023) was 50.1 ± 0.85%, showing little migration fluctuation. Women aged 15-49 accounted for 52.8 ± 10.7%, with 75.4 ± 9.7% being married. The proportion of third or higher order births averaged 1.1 ± 0.4% and showed a decreasing trend. The percentage of women aged 15-49 using contraceptive methods is high, reaching 86.0%, with condoms and oral contraceptives being the most commonly used methods. Maternal health care activities yielded some positive results: the number of medical consultations continuously increased, and the proportion of treated gynecological diseases tended to decrease, averaging 31.2 ± 5.2%. Childcare activities made significant progress: the full vaccination rate was 96.2 ± 3.3%; the proportion of children receiving near-maximum vitamin A intake reached 99.9 ± 0.27%; the rates of undernutrition by weight and height were 10.9 ± 0.9% and 21.0 ± 0.9% respectively, showing a decreasing trend over time. Conclusion: Maternal and child health care activities have achieved several outcomes such as maintaining a low rate of third or higher order births, continuous increase in medical consultations, and a decreasing trend in the proportion of treated gynecological diseases. The full vaccination rate remains high and stable, while the prevalence of undernutrition is kept low compared to the general population.